Issue evolution : race and the transformation of American politics - Carmines, Edward G. (Princeton University Press, 1989)
To test their theory of how issues can reshape the political system, Carmines and Stimson examine the impact of race on American politics in recent decades. They focus on presidential campaigns, congressional votes, party activists, and mass attitudes; and develop their alternative to realignment theory.